Noble gases of the Canadian Shield from the Lupin and Con Mines, Canada, as indicators of deep groundwater flow dynamics and residence time - Greene, Shane (University of Ottawa (Canada), 2005)
Dissolved noble gas geochemistry provides insight on origin of saline groundwaters in two Canadian Shield mines, the Lupin and Con mines in Northern Canada. Within the Con major ion and isotope geochemistry indicate groundwaters from the deepest levels sampled remain relatively undisturbed by mining. Estimates of residence time for the Con mine brines, based on radiogenically produced helium and argon, indicate a Paleozoic age, consistent with recharge during the presence of Devonian seawater in this region. This is largely corroborated by krypton and xenon concentrations which reflect concentrated brine that has equilibrated with air before infiltration. Saline waters in the Lupin mine have an age of at least 130 Ma. At the Lupin mine, neon, krypton and xenon concentrations indicate degassing has occurred, likely caused by depressurization during mining along the V1 fault/fracture zone.
Keywords: Geology.